MAKING LIGHT CONTROL DEVICE USING THE SENSOR ULTRASONIC HOUSE - Giatno Giatno; Indrianto Indrianto, SKom, MT (Jurnal Sistem Komputer, 2005)
This tool can work well when the Tran smitter and Receiver distance not exceeding three meters and without hindrance, if any obstruction depends also from the thickness and size of obstacles. The bigger and thicker main obstacle so that the distance sensor is also limited, can not be too far a way.